TRANSFORMASI PENDIDIKAN UNTUK MENGATASI KONFLIK MASYARAKAT DALAM PERSPEKTIF MULTIKULTURAL - Aidil Sudarmono (Pascasarjana IAIN Sorong, 2019)
Globalization is a process that integrates series of global life. The link between globalization and education will have new society namely a society based on